Quantifying the relative contributions of three tropical oceans to the western North Pacific anomalous anticyclone - Zhiyuan Lu; Lu Dong; Fengfei Song; Bo Wu; Shuyan Wu; Chunzai Wang (Environmental Research Letters, 2024)
The western North Pacific anomalous anticyclone (WNPAC) often exists during the mature and decaying phases of El Niño, significantly affecting the East Asian summer monsoon. Previous studies have revealed the importance of the Indian, Pacific and Atlantic Oceans in generating and maintaining the WNPAC. However, a quantitative comparison of the contributions from these three oceans is still lacking. This study uses pacemaker experiments with a state-of-the-art model to quantify the relative contributions of the three tropical oceans to the interannual WNPAC variability. We find that the Pacific accounts for over 50% of the interannual variance in boreal winter and the following spring, while the roles of the Atlantic and Indian Oceans become more pronounced in the spring. In the summer, all three oceans contribute significantly and equally. The Indian Ocean sea surface temperature is influenced by remote forcing from the Pacific Ocean, while the Atlantic Ocean operates more independently, with no evident effect from other oceans.